Hydrophobic modified ammonium polyphosphate flame-retardant coating and preparation method thereof
The in-situ coating method is used to hydrophobic modification of ammonium polyphosphate, which solves the problem of limited application in humid environments, and achieves efficient hydrophobicity and flame retardant performance improvements, and meets environmental protection requirements.
Patent Information
- Application Number
- CN202510076412.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-18
AI Technical Summary
The existing ammonium polyphosphate (APP) is limited in applications in humid environments. Due to its high hygroscopicity and low hydrophobicity, it performs poorly in some application scenarios, and traditional modification methods have environmental problems.
The in-situ coating method is used to hydrophobic modification of ammonium polyphosphate. By mixing and coating with epoxy modified silicone resin, a dense film structure is formed, thereby improving its hydrophobicity and flame retardant properties.
The excellent hydrophobicity and flame retardant properties of ammonium polyphosphate are achieved. The prepared bionic superhydrophobic halogen-free flame retardant coating is simple in process, low in cost, non-toxic and harmless, and meets the requirements of green and environmental protection.
Smart Images

Figure CN119842258A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of flame retardant materials, and particularly relates to a hydrophobically modified ammonium polyphosphate flame retardant coating and a preparation method thereof. Background Art
[0002] In recent years, ammonium polyphosphate (APP) has become a phosphorus-based flame retardant material that has attracted much attention in the field of flame retardant research. It has the advantages of low smoke and non-toxicity, high thermal decomposition temperature, low water solubility, green environmental protection, and low cost, and is therefore widely used in production and life. When APP is used as a flame retardant, it has the disadvantages of strong hygroscopicity, high addition amount, poor water resistance, poor dispersibility, poor compatibility with polymers, and limited flame retardant efficiency. These factors limit its wider application and development. In response to the above shortcomings, researchers are exploring various solutions, such as modifying APP through microencapsulation technology, surface modification technology, etc., to increase its heat resistance and stability, improve its compatibility with resins, and reduce its hygroscopicity. In addition, the development of serialized and specialized APP products is also a future development direction to meet the needs of different consumers.
[0003] A major limiting factor of APP is its high hygroscopicity, which makes it difficult to meet the use requirements in humid environments, thus limiting its application range. Therefore, the modification of APP hydrophobicity is the most important modification direction. A large number of scholars at home and abroad have studied the modification treatment methods of APP, and the common methods include microencapsulation coating modification, coupling agent modification, surfactant modification, sol-gel modification and the like.
[0004] In the article "Double-layer microencapsulation of ammoniumpolyphosphate and its enhancement on the hydrophobicity and flame retardancy of cellulose paper", Liu Kexin et al. used melamine-formaldehyde resin (MF) and silane coupling agent to successively microencapsulate ammonium polyphosphate (Si@MFAPP) and add it to the fiber suspension to prepare hydrophobic flame-retardant cellulose paper. The surface of APP is smooth and its water solubility is 0.24g / 100mL. After MF microencapsulation, the surface of MFAPP becomes rough and its solubility decreases to 0.1g / 100mL. When further coated with polysiloxane, the surface shows significantly higher roughness and forms a lotus-like microspherical structure, and its solubility decreases to 0.04g / 100mL. In addition, the residual carbon weight of Si@MFAPP at 800℃ increases from 25.27% to 38.56%. The water contact angle (WCA) of MFAPP increased from 84.23° to 90.78°, and the limiting oxygen index (LOI) increased from 31.8% to 34.1%, indicating that the flame retardancy was significantly improved. The WCA of Si@MFAPP increased to 96.45°, and the LOI increased to 34.5%, which means that the hydrophobicity and flame retardancy are further improved, and the flame retardancy and hydrophobicity of cellulose paper are significantly improved. In the study of microencapsulation modification of ammonium polyphosphate and its preparation of hydrophobic flame-retardant paper, Pan Ruidong et al. used tetraethyl orthosilicate (TEOS) and methyltriethoxysilane (MTES) as precursors, used the sol-gel method to microencapsulate APP, and prepared hydrophobic flame-retardant paper by the pulp addition method. Under alkaline conditions, TEOS and MTES jointly form dense and rough SiO 2 Shell layer, encapsulates APP into microcapsules. When the MTES addition amount is 6%, the average particle size of microencapsulated APP increases from 23.98μm to 28.52μm, WCA increases from 13.5° to 97.7°, and APP changes from hydrophilic to hydrophobic. The LOI of paper with 40% microencapsulated APP increases from 27.1% to 31.8%, and the flame retardant and hydrophobic properties of the paper are significantly improved, reaching the flame retardant level.
[0005] In the paper "Preparation and Mechanical Properties of Renewable Flame Retardant and Hydrophobic Composite Paperboard", Wan Chengjie et al. used APP-carrageenan (KC) to construct an intumescent flame retardant system (IFR), TEOS-methyltrimethoxysilane (MTMS)@magnesium aluminum hydroxide (MAH) as a synergistic flame retardant, and silane coupling agent KH550 (AEMO)@SiO 2APP-KC-[(TEOS-MTMS)@MAH]-(AEMO@SiO 2 ) composite paperboard. The flame retardant effect of the paperboard was characterized by vertical combustion test and LOI, its thermal stability was analyzed by TG, and its hydrophobicity was determined by WCA test. The test results show that when the preferred formula (the mass ratio of APP, KC, MTH, and ATH is 3:2:1:1) is used, the LOI reaches 32%, the carbonization length after the combustion experiment is 19mm, the flame duration is 0.5s, and the burning time is 3s; the TG results show that the residual carbon content is 37.5%; WCA reaches 110.2°. The prepared composite paperboard has good flame retardancy and hydrophobicity. In the article "Surface modification of ammonium polyphosphate with vinyltrimethoxysilane: Preparation, characterization, and its flame retardancy in polypropylene", Qin Zhaolu et al. modified APP with vinyltrimethoxysilane (VTMS) and applied it to polypropylene (PP) matrix. The results show that the WCA of modified APP (MAPP) increases from 9.3° to 129.7°. When MAPP is incorporated into PP / dipentaerythritol (DPER) composites instead of APP, a significant improvement in flame retardancy is observed, not only the LOI increases from 25.5% to 26.8%, but also the PP / DPER composite achieves UL-94 V-0 rating at 25% loading. The surface modification of APP by VTMS not only improves its water resistance, dispersibility and compatibility with the PP matrix, but also enhances the impact and formation of dense char due to the synergistic effect of Si, P and N, which in turn provides good protection for the underlying polymer matrix, thereby improving the flame retardant properties of PP / DPER composites.
[0006] In the article "Flame retardation of polypropylene via a novel intumescent flameretardant: Ethylene-diamine-modified ammoniumpolyphosphate", Shao Zhu-Bao et al. modified type I APP by ion exchange reaction with ethylenediamine, and the resulting modified ammonium polyphosphate (MAPP) was used alone to prepare intumescent flame-retardant PP by melt blending. The flame retardant properties of PP containing MAPP were studied by LOI method, vertical burning test and cone calorimeter (CC). The LOI of PP containing 40% MAPP reached 32.5%, which was 56.9% higher than that of PP containing the same content of APP, and its UL-94 rating reached V-0 when the sample thickness was 1.6mm, while PP containing the same content of APP had no rating. The CC test results showed that the heat release rate (HRR), mass loss rate (MLR) and smoke generation rate (SPR) of the PP / MAPP system were significantly reduced compared with pure PP and PP / APP system. In particular, the fire growth rate (FGR) and peak smoke rate of PP containing 35% MAPP were reduced by 89.1% and 63.2%, respectively, compared with PP containing 35% APP. These results indicate that PP can be successfully made flame-retardant by adding MAPP alone without additional charring agents. Dai Pei-Bang et al. successfully prepared a new type of surface-modified intumescent flame retardant composite powder (IFRC) in the "Study of surface-modified intumescent flame retardant composite powder via surfactant / polyacrylate latex and its TGcurve", which can provide good flame retardant properties without affecting the processing characteristics of thermoplastics such as acrylonitrile-butadiene-styrene copolymer (ABS). First, 3-hydroxy-2,2-bis(hydroxymethyl)propyl dihydrogen phosphate (HBPDP) was synthesized and characterized by Fourier transform infrared spectroscopy (FTIR) and nuclear magnetic resonance hydrogen spectroscopy (1HNMR). Secondly, IFRC was prepared by compounding APP, melamine, HBPDP with TX-10 surfactant / polyacrylate latex. IFRC was tested by thermogravimetric analysis, and the initial decomposition temperature was 220°C, which meets the processing temperature requirements of most thermoplastics. Finally, IFRC was added to ABS, and no milky water bath and ammonia smell were produced during blending in a twin-screw extruder, indicating that the modified IFRC has better performance during processing.
[0007] In the article "Preparation and Flame-retardant Application of Ammonium Polyphosphate Modified by Polysiloxane", Wu Cuicui et al. used TEOS and 3-aminopropyltriethoxysilane (ATOS) as raw materials, and used the sol-gel method to modify the surface of APP and flame-retardant epoxy resin. The results showed that TEOS and ATOS formed a dense polysiloxane film with micro-nanostructure similar to the surface of lotus leaves on the surface of modified APP (MAPP) through hydrolysis and polymerization. The solubility of MAPP decreased from 0.62g / 100mL to 0.18g / 100mL water, and the hydrophobicity and water resistance were significantly enhanced. In the study "Study on sol-gel-modifiedammoniumpolyphosphate and its application in the flame-retardantpolyurethanecomposites", Zeng Fanchao et al. used TEOS and vinyltriethoxysilane (VTS) as precursors to prepare organic-inorganic modified APP flame retardant by sol-gel method. Modified APP (VTSAPP) was then added to polyurethane (PU) to prepare flame-retardant PU / VTSAPP composites. Crucially, the structure and properties of VTSAPP were systematically characterized. The results showed that a dense hybrid silicone layer structure was formed on the surface of APP. The LOI of the PU / 20VTSAPP composite increased from 19.5% of pure PU to 30%, and the UL-94 test level reached V-0. In addition, compared with APP, the addition of VTSAPP significantly reduced the smoke release during PU combustion. The P and Si compounds in VTSAPP help to form a more continuous and denser char layer and improve the thermal stability of the char layer, clearly confirming that VTSAPP is an effective PU flame retardant.
[0008] In summary, the current technology mainly uses two methods to improve the surface hydrophobicity of APP: surface modification with coupling agents and microencapsulation coating. When preparing modified APP, the existing coupling agent surface treatment process has limitations. Because the formed coating film is not dense enough, the anti-migration performance of the modified APP in the polymer matrix is not ideal, so that its water solubility is still high. Although microencapsulation technology can reduce water solubility to a certain extent, the capsule wall materials used in this method, such as melamine-formaldehyde resin, urea-formaldehyde and phenolic resin, may release formaldehyde during production and use, causing environmental problems. Therefore, developing a modified APP with lower surface polarity and water solubility, ensuring that it has low migration ability in a humid environment and has excellent environmental performance, is still an important technical challenge facing this field. Summary of the invention
[0009] In view of the above-mentioned deficiencies in the prior art, the present invention provides a hydrophobically modified ammonium polyphosphate flame retardant coating and a preparation method thereof. The present invention utilizes a simple and easy-to-operate in-situ coating method to hydrophobically modify ammonium polyphosphate, and further prepares a bionic super-hydrophobic halogen-free flame retardant coating based on the hydrophobic modification of ammonium polyphosphate as the main formula. The bionic super-hydrophobic coating has a simple preparation process, low cost, and is non-toxic and harmless, meeting green environmental protection requirements.
[0010] To achieve the above purpose, the technical solution adopted by the present invention to solve the technical problem is:
[0011] A method for hydrophobically modifying ammonium polyphosphate comprises the following steps:
[0012] (1) mixing ammonium polyphosphate and epoxy-modified silicone resin in a mass ratio of 1 to 2:1, and then dissolving them in an organic solvent;
[0013] (2) placing the solution at a constant temperature of 80 to 120° C. for coating reaction;
[0014] (3) After the reaction is completed, the mixture is washed, dried at 80 to 90° C. for 4 to 6 hours, and crushed to obtain hydrophobically modified ammonium polyphosphate.
[0015] Furthermore, the epoxy-modified silicone resin is phenylmethyl epoxy-modified silicone resin, aminophenol epoxy-modified silicone resin, diaminodiphenylmethane epoxy-modified silicone resin, polyisocyanurate-oxazolidone resin, chloropropane bisphenol epoxy-modified silicone resin or p-aminophenol epoxy-modified silicone resin.
[0016] Furthermore, in step (1), the mass ratio of ammonium polyphosphate to epoxy-modified silicone resin is 2:1.
[0017] Furthermore, the reaction temperature in step (1) is 90-100°C.
[0018] Furthermore, the coating reaction in step (2) is carried out in a closed environment or under oil bath conditions, and the reaction time is 8 to 15 hours.
[0019] Furthermore, the organic solvent is ethyl acetate.
[0020] A method for preparing a bionic super-hydrophobic APP flame-retardant coating comprises the following steps:
[0021] (1) Hydrophobically modified ammonium polyphosphate
[0022] The hydrophobically modified ammonium polyphosphate is prepared by the above method;
[0023] (2) Preparation of flame retardant coatings
[0024] The epoxy-modified silicone resin, polydimethylsiloxane siloxane, titanium dioxide, hydrophobically modified ammonium polyphosphate and diatomaceous earth are mixed and dissolved, and stirred at room temperature for 1 to 3 hours to prepare a flame retardant coating.
[0025] Furthermore, in step (2), the mass ratio of epoxy-modified silicone resin, polydimethylsiloxane siloxane, titanium dioxide, hydrophobically modified ammonium polyphosphate and diatomaceous earth is 1-3:0.5-1:1-2:3-5:0.5-1.
[0026] A bionic super-hydrophobic APP flame-retardant coating is prepared by adopting the method.
[0027] A bionic super-hydrophobic APP flame-retardant coating, comprising the following components in parts by weight:
[0028] 25-30 parts of epoxy modified silicone resin (EMSR), 5-10 parts of polydimethylsiloxane siloxane (PDMS), 15-20 parts of titanium dioxide, 40-50 parts of hydrophobically modified ammonium polyphosphate (HMAPP) and 5-10 parts of diatomaceous earth (DE).
[0029] Beneficial effects of the present invention:
[0030] The present invention utilizes a simple and easy-to-operate in-situ coating method to hydrophobically modify ammonium polyphosphate. The modified ammonium polyphosphate has excellent hydrophobicity and flame retardant properties. The bionic super-hydrophobic halogen-free flame retardant coating is further prepared using the modified ammonium polyphosphate as a main formula. The flame retardant coating has a simple preparation process, low cost, is non-toxic and harmless, and meets green environmental protection requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The wettability and water static contact angle experiments of HMAPP provided in Example 1;
[0032] Figure 2 The wettability and water static contact angle experiments of II-APP provided for Comparative Example 1;
[0033] Figure 3 The wettability and water static contact angle experiment of the super hydrophobic coating sample steel plate provided in Example 11;
[0034] Figure 4 The back plate temperature variation curves of the blank steel plate and the super hydrophobic coating sample steel plate provided in Example 11;
[0035] Figure 5 This is an infrared thermal image of the super-hydrophobic coating sample steel plate provided in Example 11. DETAILED DESCRIPTION
[0036] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.
[0037] Example 1
[0038] A method for hydrophobic modification of ammonium polyphosphate, the specific process is as follows:
[0039] Weigh 50g of II-APP and 25g of phenylmethyl epoxy modified silicone resin into a beaker, add 100mL of ethyl acetate, and stir with a stirrer at 800r / min for 1h; transfer the above solution to a 200mL polytetrafluoroethylene-lined reactor and seal it with a stainless steel sealing sleeve, then place it in a 90℃ oven, maintain a constant temperature for reaction and continue for 10h; take out the reactor, cool it to room temperature, vacuum filter and wash it with ethyl acetate for several times; place the washed product in an 80℃ oven to dry for 4h, and finally grind it into powder.
[0040] Example 2
[0041] A method for hydrophobic modification of ammonium polyphosphate, the specific process is as follows:
[0042] Weigh 40g of II-APP and 25g of p-aminophenol epoxy-modified silicone resin into a beaker, add 100mL of ethyl acetate, and stir with a stirrer at 800r / min for 1h; transfer the above solution to a 200mL polytetrafluoroethylene-lined reactor and seal it with a stainless steel sealing sleeve, then place it in an 80℃ oven, maintain a constant temperature for reaction and continue for 10h; take out the reactor, cool it to room temperature, vacuum filter and wash it with ethyl acetate for several times; place the washed product in an 80℃ oven to dry for 4h, and finally grind it into powder.
[0043] Example 3
[0044] A method for hydrophobic modification of ammonium polyphosphate, the specific process is as follows:
[0045] Weigh 35g of II-APP and 25g of diaminodiphenylmethane epoxy-modified silicone resin into a beaker, add 100mL of ethyl acetate, and stir with a stirrer at 800r / min for 1h; transfer the above solution to a 200mL polytetrafluoroethylene-lined reactor and seal it with a stainless steel sealing sleeve, then place it in a 90℃ oven, maintain a constant temperature for reaction and continue for 12h; take out the reactor, cool it to room temperature, vacuum filter and wash it with ethyl acetate for several times; place the washed product in an 80℃ oven to dry for 4h, and finally grind it into powder.
[0046] Example 4
[0047] A method for hydrophobic modification of ammonium polyphosphate, the specific process is as follows:
[0048] Weigh 50g of II-APP and 25g of polyisocyanurate-oxazolidone resin into a beaker, add 100mL of ethyl acetate, and stir with a stirrer at 800r / min for 1h; transfer the above solution to a 200mL polytetrafluoroethylene-lined reactor and seal it with a stainless steel sealing sleeve, then place it in a 120℃ oven, maintain a constant temperature for reaction and continue for 10h; take out the reactor, cool it to room temperature, vacuum filter and wash it with ethyl acetate for several times; dry the washed product in an 80℃ oven for 4h, and finally grind it into powder.
[0049] Example 5
[0050] A method for hydrophobic modification of ammonium polyphosphate, the specific process is as follows:
[0051] Weigh 50g of II-APP and 25g of chloropropane bisphenol epoxy modified silicone resin into a beaker, add 100mL of ethyl acetate, and stir with a stirrer at 800r / min for 1h; transfer the above solution to a 200mL polytetrafluoroethylene-lined reactor and seal it with a stainless steel sealing sleeve, then place it in a 90℃ oven, maintain a constant temperature for reaction and continue for 8h; take out the reactor, cool it to room temperature, vacuum filter and wash it with ethyl acetate for several times; place the washed product in an 80℃ oven to dry for 4h, and finally grind it into powder.
[0052] Example 6
[0053] A method for hydrophobic modification of ammonium polyphosphate, the specific process is as follows:
[0054] Weigh 50g of II-APP and 25g of phenylmethyl epoxy modified silicone resin into a beaker, add 100mL of ethyl acetate, and stir evenly with a stirrer; transfer the above solution to a heating reflux device with a 200mL flask and a condenser, then place it in a 90°C oil bath for reaction and stir at 800r / min for 6h; cool to room temperature, vacuum filter and wash with ethyl acetate for several times; place the washed product in an oven at 80°C to dry for 4h, and finally grind it into powder.
[0055] Example 7
[0056] A method for hydrophobic modification of ammonium polyphosphate, the specific process is as follows:
[0057] Weigh 50g of II-APP and 25g of p-aminophenol epoxy-modified silicone resin into a beaker, add 100mL of ethyl acetate, and stir evenly with a stirrer; transfer the above solution to a heating reflux device with a 200mL flask and a condenser, then place it in a 90°C oil bath for reaction and stir at 800r / min for 6h; cool to room temperature, vacuum filter and wash with ethyl acetate for several times; place the washed product in an oven at 80°C to dry for 4h, and finally grind it into powder.
[0058] Example 8
[0059] A method for hydrophobic modification of ammonium polyphosphate, the specific process is as follows:
[0060] Weigh 50g of II-APP and 25g of diaminodiphenylmethane epoxy-modified silicone resin into a beaker, add 100mL of ethyl acetate, and stir evenly with a stirrer; transfer the above solution to a heating reflux device with a 200mL flask and a condenser, then place it in a 90°C oil bath for reaction and stir at 800r / min for 6h; cool to room temperature, vacuum filter and wash with ethyl acetate for several times; place the washed product in an oven at 80°C to dry for 4h, and finally grind it into powder.
[0061] Example 9
[0062] A method for hydrophobic modification of ammonium polyphosphate, the specific process is as follows:
[0063] Weigh 50g of II-APP and 25g of polyisocyanurate-oxazolidone resin into a beaker, add 100mL of ethyl acetate, and stir evenly with a stirrer; transfer the above solution to a heating reflux device with a 200mL flask and a condenser, then place it in a 90℃ oil bath for reaction and stir at 800r / min for 6h; cool to room temperature, vacuum filter and wash with ethyl acetate for several times; place the washed product in an oven at 80℃ to dry for 4h, and finally grind it into powder.
[0064] Example 10
[0065] A method for hydrophobic modification of ammonium polyphosphate, the specific process is as follows:
[0066] Weigh 50g of II-APP and 25g of chloropropane bisphenol epoxy modified silicone resin into a beaker, add 100mL of ethyl acetate, and stir evenly with a stirrer; transfer the above solution to a heating reflux device with a 200mL flask and a condenser, then place it in a 90℃ oil bath for reaction and stir at 800r / min for 6h; cool to room temperature, vacuum filter and wash with ethyl acetate for several times; place the washed product in an 80℃ oven to dry for 4h, and finally grind it into powder.
[0067] Embodiment 11
[0068] A bionic super-hydrophobic APP flame-retardant coating, the preparation method of which is as follows:
[0069] Take 30g EMSR and 10g PDMS, add them into 100mL ethyl acetate and fully dissolve them; add 20g HMAPP prepared in Example 1, 20g TiO 2 and 10 g DE, and stirred with a stirrer at 1000 r / min for 1 h at room temperature to prepare the bionic superhydrophobic APP flame retardant coating.
[0070] Then the flame retardant coating prepared above is sprayed onto the steel plate, and the specific process is as follows:
[0071] Use a spray gun with a caliber of 1.5mm, set the spray pressure to 0.2-0.5MPa, the spray angle to 45°, the distance between the spray gun mouth and the fixed stainless steel plate to 10-15cm, and spray from left to right and from top to bottom. After spraying, let it stand at room temperature for 10 minutes; place the sample steel plate in a vacuum drying oven at 120℃ for 2 hours; then cool it to room temperature and seal it for storage.
[0072] Example 12
[0073] A bionic super-hydrophobic APP flame-retardant coating, the preparation method of which is as follows:
[0074] Take 30g EMSR and 10g PDMS, add them into 100mL ethyl acetate and fully dissolve them; add 20g HMAPP prepared in Example 6, 20g TiO 2 and 10 g DE, and stirred with a stirrer at 1000 r / min for 1 h at room temperature to prepare the bionic superhydrophobic APP flame retardant coating.
[0075] Then the flame retardant coating prepared above is sprayed onto the steel plate, and the specific process is as follows:
[0076] Use a roller brush with a length of 15 cm and a diameter of 5 cm to roll 6-8 layers on the stainless steel plate in the order of two adjacent layers vertically crossed. After coating, let it stand at room temperature for 10 minutes; place the sample steel plate in a vacuum drying oven at 120°C for 2 hours; then cool it to room temperature and seal it for storage.
[0077] Embodiment 13
[0078] A bionic super-hydrophobic APP flame-retardant coating, the preparation method of which is as follows:
[0079] Take 30g EMSR and 10g PDMS, add them into 100mL ethyl acetate and fully dissolve; add 20g HMAPP prepared in Example 9, 20g TiO 2and 10 g DE, and stirred with a stirrer at 1000 r / min for 1 h at room temperature to prepare the bionic superhydrophobic APP flame retardant coating.
[0080] Then the flame retardant coating prepared above is sprayed onto the steel plate, and the specific process is as follows:
[0081] Use a rubber scraper with a length of 15 cm to scrape 6-8 layers on the stainless steel plate in the order of two adjacent layers vertically crossed. After coating, let it stand at room temperature for 10 minutes; place the sample steel plate in a vacuum drying oven at 120℃ for 2 hours; then cool it to room temperature and seal it for storage.
[0082] Comparative Example 1
[0083] Take 2g of unmodified II-APP and place it on a water table and gently compact it, drop Sudan III dyed water on its surface and observe the morphology of the water drop. Place a small amount of II-APP on a contact angle tester and measure its static WCA.
[0084] Comparative Example 2
[0085] Take 5g of II-APP and evenly disperse it in 400mL of ethanol-water mixed solution (volume ratio is 2:8), stir it at 300r / min in a constant temperature water bath at 30℃, then take 5g of cationic emulsion and add it to the evenly dispersed APP suspension, continue heating and stirring for 30min, then filter, wash and dry to obtain surface hydrophobic modified APP (MAPP). (Synthesis of cationic emulsion: Add styrene, allyl hexanoate, ethylene glycol dimethacrylate, hexadecyltrimethylammonium chloride and deionized water into a three-necked flask, place it in a constant temperature water bath at 30℃, N 2 In an atmosphere, pre-emulsify at a stirring speed of 200 r / min for 30 minutes, then heat to 70°C, slowly drop a certain amount of 2,2'-azobisisobutylamidine dihydrochloride solution and keep warm for 2 hours. Butyl acrylate, butyl methacrylate, glycidyl methacrylate, hexadecyltrimethylammonium chloride and deionized water were mixed and stirred at 30°C and N 2 In an atmosphere, pre-emulsify at a stirring speed of 500r / min for 30min, then slowly add a certain amount of 2,2'-azobisisobutylamidine dihydrochloride solution to the system after the first step of the reaction, and keep the reaction warm for 3h. Cool naturally to room temperature and discharge to obtain a cationic emulsion. ) Place a small amount of MAPP on a contact angle tester to measure its static WCA.
[0086] Comparative Example 3
[0087] 20 g of styrene, 5 g of butyl methacrylate, 8 g of allyl hexanoate, 1 g of ethylene glycol dimethacrylate, 5 g of hexadecyltrimethylammonium chloride (CTAC) and 100 g of deionized water were mixed to prepare solution A;
[0088] Mix 0.2 g of 2,2-azo(2-methylpropylimidazole) dihydrochloride (AIBA) with 10 g of deionized water to prepare solution B;
[0089] 15 g of butyl acrylate, 5 g of glycidyl methacrylate, 2 g of CTAC, 0.2 g of AIBA and 40 g of deionized water were mixed to prepare solution C;
[0090] Pour all of solution A into a 250 ml three-necked flask and, while stirring and passing N 2 When the temperature reaches 40℃, stop heating. 2 After solution A is heated to 60°C, solution B is slowly added dropwise to solution A over 30 min using a dropping funnel; the temperature of the mixed solution A and B is continued to be maintained at 60°C, and solution C is slowly added to the mixed solution over 90 min to obtain an emulsion.
[0091] Prepare 350g of ethanol-water solution (mass ratio is 2:8); mix 10g of II-APP, 24g of emulsion and 350g of ethanol-water solution in a 500ml three-necked flask, stir at 300r / min for 1h in a 30℃ constant temperature water bath, filter after reaction, and dry at 120℃ for 2h to obtain surface hydrophobic modified APP. Place a small amount of surface hydrophobic modified APP on a contact angle tester to measure its static WCA.
[0092] 1. The contact angles of the hydrophobically modified APPs prepared in Examples 1 to 10 and the products of Comparative Examples 1 to 3 were measured. The results are shown in Table 1.
[0093] Table 1 Contact angles of APP prepared by different methods
[0094] experiment Contact angle experiment Contact angle experiment Contact angle Comparative Example 1 0° Example 1 117.5° Example 6 117.2° Comparative Example 2 89.6° Example 2 117.3° Example 7 117.1° Comparative Example 3 105.2° Example 3 117.3° Example 8 117.2° Example 4 117.0° Example 9 116.9° Example 5 117.2° Example 10 117.3°
[0095] 2. The modified APP, carbon-forming agent and wollastonite prepared in Examples 1-10 and Comparative Examples 1-3 were uniformly mixed in a mass ratio of 9:2:1; 2.2 g of the above mixed powder was mixed with 7.8 g of PP, and the modified APP / PP strips were injection molded using a mold using a micro injection molding machine, and then the injection molded strips were subjected to a limiting oxygen index (LOI) test according to GB / T 2406.2-2009; the injection molded strips were subjected to a vertical burning test (UL-94) according to GB / T 2408-2021, and the results are shown in Table 2.
[0096] Table 2 LOI and UL-94 test
[0097] Spline LOI UL-94 Pure PP 17.8% none Ⅱ-APP / PP (Comparative Example 1) 23.3% V-1 Modified APP / PP (Comparative Example 2) 26.1% V-0 Modified APP / PP (Comparative Example 3) 28.5% V-0 HMAPP / PP (Example 1) 35.2% V-0 HMAPP / PP (Example 2) 34.9% V-0 HMAPP / PP (Example 3) 34.6% V-0 HMAPP / PP (Example 4) 34.7% V-0 HMAPP / PP (Example 5) 34.4% V-0 HMAPP / PP (Example 6) 35.1% V-0 HMAPP / PP (Example 7) 34.6% V-0 HMAPP / PP (Example 8) 34.3% V-0 HMAPP / PP (Example 9) 35.0% V-0 HMAPP / PP (Example 10) 34.9% V-0
[0098] According to the test results in Table 1 and Table 2, compared with the technical solution provided in the comparative example, the hydrophobically modified APP prepared by the technical solution of the present invention has more excellent hydrophobicity and more excellent flame retardant properties.
[0099] 3. Place the sample steel plate prepared in Example 11 on a horizontal surface, drop water, milk, cola and tea on the surface, and observe the morphology of the droplets. Place a small amount of the sample steel plates prepared in Examples 11-13 on a contact angle tester, and perform a water contact angle test on the prepared steel structure fire retardant coating according to GB / T 42694-2023. The results are shown in Table 1. Figure 3 .
[0100] 4. The sample steel plate prepared in Example 11 was placed on a fire resistance test workbench. According to GB 14907-2018, a spray gun with an outer flame temperature of about 600°C was used to perform a fire resistance test on a blank steel plate and a sample steel plate coated with a super-hydrophobic coating. An infrared temperature measuring gun was used to record the temperature of the steel plate back plate every 5 minutes. The results are shown in Table 1. Figure 4 and Figure 5 .
[0101] like Figures 3 to 5 As shown, it is shown that the flame retardant coating prepared by the technical solution of the present invention has excellent hydrophobic, heat-resistant and flame-retardant properties.
[0102] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A method for hydrophobic modification of ammonium polyphosphate, characterized in that: The following steps are involved: (1) mixing ammonium polyphosphate and epoxy-modified silicone resin in a mass ratio of 1 to 2:1, and then dissolving them in an organic solvent; (2) placing the solution at a constant temperature of 80 to 120° C. for coating reaction; (3) After the reaction is completed, the mixture is washed, dried at 80 to 90° C. for 4 to 6 hours, and crushed to obtain hydrophobically modified ammonium polyphosphate.
2. The method according to claim 1, characterized in that The epoxy-modified silicone resin is phenylmethyl epoxy-modified silicone resin, aminophenol epoxy-modified silicone resin, diaminodiphenylmethane epoxy-modified silicone resin, polyisocyanurate-oxazolidone resin, chloropropane bisphenol epoxy-modified silicone resin or p-aminophenol epoxy-modified silicone resin.
3. The method according to claim 1, characterized in that In step (1), the mass ratio of ammonium polyphosphate to epoxy-modified silicone resin is 2:
1.
4. The method according to claim 1, characterized in that: The reaction temperature in step (1) is 90-100°C.
5. The method according to claim 1, characterized in that Step (2) is to carry out the coating reaction in a closed environment or under oil bath conditions, and the reaction time is 8 to 15 hours.
6. The method according to claim 1, characterized in that The organic solvent is ethyl acetate.
7. A method for preparing a bionic super-hydrophobic APP flame-retardant coating, characterized in that: The following steps are involved: (1) Hydrophobically modified ammonium polyphosphate The hydrophobically modified ammonium polyphosphate is prepared by the method according to any one of claims 1 to 6; (2) Preparation of flame retardant coatings The epoxy-modified silicone resin, polydimethylsiloxane siloxane, titanium dioxide, hydrophobically modified ammonium polyphosphate and diatomaceous earth are mixed and dissolved, and stirred at room temperature for 1 to 3 hours to prepare a flame retardant coating.
8. The preparation method according to claim 7, characterized in that: In step (2), the mass ratio of epoxy-modified silicone resin, polydimethylsiloxane siloxane, titanium dioxide, hydrophobically modified ammonium polyphosphate and diatomaceous earth is 1-3:0.5-1:1-2:3-5:0.5-1.
9. A bionic super-hydrophobic APP flame-retardant coating, characterized in that: It is prepared by the method described in claim 7 or 8.
10. A bionic super-hydrophobic APP flame-retardant coating, characterized in that: It includes the following components in parts by weight: 25-30 parts of epoxy-modified silicone resin, 5-10 parts of polydimethylsiloxane siloxane, 15-20 parts of titanium dioxide, 40-50 parts of hydrophobically modified ammonium polyphosphate and 5-10 parts of diatomaceous earth.
Citation Information
Cited By
A photothermal dual-trigger self-repairing gradient water-retention composite fire extinguishing material and a preparation method thereof
CN122849712A